2015
DOI: 10.1111/fwb.12576
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effects of effluents from a wastewater treatment plant on river ecosystem metabolism: subsidy or stress?

Abstract: SUMMARY1. The effluents of wastewater treatment plants (WWTPs) include a complex mixture of nutrients and pollutants. Nutrients can subsidise autotrophic and heterotrophic organisms, while toxic pollutants can act as stressors, depending, for instance, on their concentration and interactions in the environment. Hence, it is difficult to predict the overall effect of WWTP effluents on river ecosystem functioning. 2. We assessed the effects of WWTP effluents on river biofilms and ecosystem metabolism in one rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
57
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 77 publications
11
57
2
5
Order By: Relevance
“…The DOC in the Panke river was in accordance with the results of Aristi et al [40], who found higher DOC values near a WWTP which decreased with increasing distance to the plant, and a several-fold increase in the DOC concentration caused by a WWTP effluent was also observed by Ruggiero et al [41]. In our study, higher DOC concentrations were found mainly at the PuBG and the PoBG site, within the summer campaign 2017.…”
Section: Discussionsupporting
confidence: 92%
“…The DOC in the Panke river was in accordance with the results of Aristi et al [40], who found higher DOC values near a WWTP which decreased with increasing distance to the plant, and a several-fold increase in the DOC concentration caused by a WWTP effluent was also observed by Ruggiero et al [41]. In our study, higher DOC concentrations were found mainly at the PuBG and the PoBG site, within the summer campaign 2017.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, variation (over time) in the number and concentration of compounds found in water would have likely altered BAFs if a longer time window had been considered. However, levels found in river water were close to those found in the same site but in a different period of the year , and another study showed that the concentrations of some pharmaceuticals in these study reaches were relatively stable over a 48-h period (Aristi et al, 2015). Overall, our study advances the notion that both waterborne and dietary exposure may contribute to the bioaccumulation of emerging pollutants in aquatic organisms.…”
Section: Discussionsupporting
confidence: 84%
“…Numerous studies have reported the existence of fungi in pollution‐stressed and extreme environments (Aguilera, ; Aristi et al., ; Cantrell, Casillas‐Martínez, & Molina, ; Cantrell et al., ). Aspergillus , Penicillium , Curvularia , Fusarium , Microsporum , Trichoderma , Rhizoctonia , Nigrospora , and Chaetophoma have previously been isolated from raw refinery effluents (Machido, Yakubu, & Ezeonuegbu, ).…”
Section: Discussionmentioning
confidence: 99%